1984
DOI: 10.1136/adc.59.10.940
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and respiratory symptoms in primary school.

Abstract: SUMMARY The association of weight for height and triceps skinfold with seven respiratory symptoms has been examined using logistic regression analysis in 7800 5 to 11 year old children (6200 in England and 1600 in Scotland). The (SDS).10 " The SDS is calculated for each child as the difference between his or her measurement and the average measurement of a population of the same age, sex, and country divided by the standard deviation of the measurement for that population. Here overweight and underweight re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 11 publications
2
33
0
4
Order By: Relevance
“…Parallel increases in the prevalence of asthma and in obesity have been reported in affluent countries, and an association between obesity and asthma has recently been observed among both children [25,26] and adults [11,12]. The associations are not consistent, since one study reported an association between obesity and asthma or wheezing, but not airway hyperresponsiveness, which is closely associated with asthma [12].…”
Section: Discussionmentioning
confidence: 80%
“…Parallel increases in the prevalence of asthma and in obesity have been reported in affluent countries, and an association between obesity and asthma has recently been observed among both children [25,26] and adults [11,12]. The associations are not consistent, since one study reported an association between obesity and asthma or wheezing, but not airway hyperresponsiveness, which is closely associated with asthma [12].…”
Section: Discussionmentioning
confidence: 80%
“…A larger population might be required to evaluate the effect of overweight in asthma and atopic dermatitis separately. Previous studies on overweight and allergy showed conflicting results (Somerville et al, 1984;Schwartz et al, 1990;Gold et al, 1993;Luder et al, 1998;Huang et al, 1999;CastroRodriguez et al, 2001;Chinn & Rona, 2001). Among recent studies, the 5-y prospective Children's Health Study showed that overweight and obese boys, but not girls, were at a higher risk of new-onset asthma (Gilliland et al, 2003); Schachter et al (2003) found that BMI was positively associated with atopy, wheeze and cough but not airway obstruction and airway hyperresponsiveness in 7-to 12-y-old girls, while no association was observed in boys; Romieu et al (2004) reported that a higher BMI was associated with an increased risk of asthma and wheeze in 6-to 16-y-old children and adolescents from the US Third National Health and Nutrition Survey (NHANES III); and To et al (2004) found no association between BMI and asthma among 4-to 11-yold Canadian children.…”
Section: Discussionmentioning
confidence: 95%
“…37 Although parallel increases in the prevalence of obesity and asthma in Western countries have been reported, it remains to be determined whether this association is causal or by chance. 38 Although obesity may simply be a marker of recently adopted lifestyle habits also associated with asthma, several specific mechanisms can be proposed for their association, 39 and it is now recognized that a causal relation may exist between them.…”
mentioning
confidence: 99%